A comparative analysis of elasticity modulus of recycled aggregate concrete with silica fume - Cakir, Ozgur; Dilbas, Hasan (PAMUKKALE UNIV, 2018)
Recycling of waste materials has significant influence on the concept of sustainability in construction industry due to the conservation of natural resources and minimizing the environmental impacts which leads to habitable future. Construction activities, in general, result in huge amount of construction and demolition waste (C&DW) and C&DW has a great potential for possible disposal as recycled aggregate (RA) in civil engineering applications, especially in recycled aggregate concrete (RAC), after recycling processes. In this concept, concrete mixtures including RA and silica fume (SF) at various ratios (0-30-40-70-100%) and (0-5-10%), respectively, are produced in order to determine the elasticity modulus of RAC. This work aims to examine elasticity modulus of RAC determined according to the formulas of standards and studies. Analytical and statistical assessments are performed and experimental and theoretical results are compared. When RA content increases, the elasticity modulus decreases. SF utilization in RAC improves the mechanical parameters (elasticity modulus and compressive strength). The American standard (ACI 318-05) predicts the elasticity modulus approximately to the experimental results although it has the highest relative standard deviations in comparison to the regarded standards. Moreover, proposed equations for RAC by researchers estimate the elasticity modulus values greater than those of standards and the experimental results. An elasticity modulus equation is also proposed for RAC with and without SF.
Keywords: Recycled aggregate concrete; Silica fume; Elasticity modulus; Standards; MECHANICAL-PROPERTIES; DEMOLITION WASTE; STRENGTH; PERFORMANCE; Engineering